Assays for Determination of Protein Concentration. Issue 1 (1st June 2016) - Olson, Bradley J.S.C.
Abstract: Biochemical analysis of proteins relies on accurate quantification of protein concentration. Detailed in this appendix are some commonly used methods for protein analysis, e.g., Lowry, Bradford, bicinchoninic acid (BCA), UV spectroscopic, and 3‐(4‐carboxybenzoyl)quinoline‐2‐carboxaldehyde (CBQCA) assays. The primary focus of this report is assay selection, emphasizing sample and buffer compatibility. The fundamentals of generating protein assay standard curves and of data processing are considered, as are high‐throughput adaptations of the more commonly used protein assays. Also included is a rapid, inexpensive, and reliable BCA assay of total protein in SDS‐PAGE sample buffer that is used for equal loading of SDS‐PAGE gels. © 2016 by John Wiley & Sons, Inc.